Optimal Operation of Coupled Distribution System and Traffic System using Traffic Flow and OPF Analysis. (February 2019) - Li, Peiling; Wang, Guibin; Wang, Huaizhi; Fu, Zhongxue; Wu, Chao
Abstract: With the support of the national policy, the number of electric vehicles (EVs) has increased rapidly in recent years. The distribution system (DS) and traffic system (TS) have been operated independently for many years, but the operation of those two systems should consider the impact of fast growing EVs. The research in this paper analyzes the influence of EVs in the DS and the TS with multiple travel situations including different traffic flow sizes and congestion severity levels. A social cost model is proposed in this paper considering traffic flow and optimal power flow (OPF) to calculate a total social cost of a system composed of the 25-node TS and the 30-node DS. In the case study, the impact of different traffic flow sizes and different congestion conditions on the proposed model is compared.